Fashion drawing skills training for unqualified fashion entrepreneurs in the Emfuleni Local Municipality: a needs assessment - Strydom, Le-nika (Vaal University of Technology, 2019)
INTRODUCTION AND BACKGROUND The fashion trade is a global industry (Amankhwah, Badoe & Chichi 2014:144) that plays a major role in the socio-economic development of many countries (Sarpong, Howard & Osei-Ntiri 2011:98). A number of Asian countries, for example, have been known to thrive in the international textile and fashion trade, owing to their successful training programs in fashion and apparel design (Maiyo, Abong’o & Tuigon’g 2014:63). In South Africa (SA) fashion is also seen as an important industry, as it forms part of economic development programs (Dlodlo 2014:191) and aids in income generation for individuals, not only in major cities, but also in smaller towns and peri-urban areas. Thus, the statement can be made that the successful training of individuals through training programs (with regard to fashion-related skills) has a direct link to a thriving fashion industry and a direct impact on individuals, group and community income generation. Nonetheless, not all individuals within the fashion industry have acquired formal fashion training. Some may have obtained fashion-related skills (such as sewing, pattern making and fashion drawing) through family members, short courses, school or in-service work experience elsewhere. These skills, particularly fashion drawing and illustration (hereafter referred to as fashion drawing), are necessary visual communication tools with which the designer relays their ideas and designs to the client. Visual communication is a pictorial form of communication where visual symbols are incorporated in order to convey information (Liu 2015:41) and this process of visual communication enables both parties to be equally clear about the proposed design (Tatham & Seaman 2004:114; Calderin 2013:148). Thus, specifically in relation to the field of fashion, visual communication is used to communicate designs or ideas to individuals in a visual manner by making use of sketches, photographs, drawings, etc. However, in a previous study conducted in the Sedibeng District Municipality (SDM) (Van Wyk 2007:78), it was found that the most prominent skill that fashion entrepreneurs felt they needed, but lacked, is that of fashion drawing. Of the total sample population, 19% indicated that they do not possess fashion drawing skills. Although this is not a significantly high number, it is important to note that 66% of the mentioned study’s respondents had obtained qualifications from tertiary institutions (Van Wyk 2007:77), which would in all probability have included a fashion drawing curriculum. The lack of drawing skills could be problematic, as this lack relates to client satisfaction which, in turn, promotes the success of entrepreneurial endeavours (Burns & Bryant 2002:42). To address this, the current study was aimed at determining the level, nature and type of fashion drawing applied by fashion entrepreneurs with no formal fashion-related training (FEWNFFRT)1 within the Emfuleni Local Municipality (ELM). This ascertainment was completed in terms, specifically, of the following: the use of fashion sketches to visually communicate the design of the garment to the client; the challenges experienced by the fashion entrepreneurs when communicating an idea or design to a client; and the need for training in fashion drawing as a means of visual communication. A quantitative, non-experimental needs assessment was conducted among a group of FEWNFFRT within the ELM. It is important for the reader to note that this specific research study formed part of a larger study, in which the data was gathered in a joint manner with another researcher (whose study focussed on the business skills training needs for FEWNFFRT in the ELM). To clarify, data was collected and analysed together, but the interpretation and application of the data differed due to different research questions, focus and context. Therefore, while the same data was gathered and used in conjunction with another researcher, it should be noted that this study followed a unique angle. The reason for the joint data collection was dictated by the specific constraint of the study in terms of the specific inclusion criteria to which the sample population had to adhere. Interviewer-administered questionnaires were employed in order to gather data from respondents. This type of data collection tool was seen as the most appropriate for the collection of data for this study, as it was conducted in a verbal manner and allowed the interviewer to explain questions and instruction to the respondents in cases where questions were in any way unclear or the respondents were uncertain. This in turn ensured a higher response rate and enhanced the quality of the data gathered. Insight gained from this study aided in generating a new understanding of the fashion drawing skills training needs of fashion entrepreneurs in the ELM region, which may guide future research aimed at developing training programs, materials and interventions with regard to fashion drawing skills.
M. Tech. (Department of Visual Arts and Design: Fashion, Faculty of Human Sciences), Vaal University of Technology.
Keywords: Fashion drawing skills; Training; Entrepreneurs; Fashion entrepreneurs; Visual communication; Dissertations, Academic -- South Africa.; Entrepreneurship -- South Africa.; Fashion merchandising -- South Africa.; Fashion design.; Fashion drawing.